Introduction to the Special Issue: Behavioral Interventions to Enhance Academic Outcomes. (January 2015) - Lang, Russell; Rispoli, Mandy
The purpose of Behavior Modification' s special issue on academics is to feature a collection of studies involving behavioral interventions designed to improve academic outcomes. Studies published in this special issue address a variety of academic subjects (e.g., reading, science, social studies) for students with learning, emotional, behavioral, and developmental disabilities. A total of three rigorous literature reviews and six well-designed intervention studies are presented. The studies included in the special issue clearly illustrate the potential benefit of behavioral interventions designed to improve academic performance and related behaviors (e.g., task engagement, school readiness).